2007
DOI: 10.2514/1.23507
|View full text |Cite
|
Sign up to set email alerts
|

Separation Control by Self-Activated Movable Flaps

Abstract: Separation control is an important issue in the physiology of birdflight. Here, the adaption of the separation control mechanism by bird feathers to the requirements of engineering applications is described in detail. Self-activated movable flaps similar to artificial bird feathers represent a high-lift system for increasing the maximum lift of airfoils. Their effect on the unsteady flow around a two-dimensional airfoil configuration is investigated by a joint numerical and experimental study. First, attention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
55
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 5 publications
12
55
0
Order By: Relevance
“…Thus, this feature of automatic activation, as opposed to active control techniques which require an energy input to come into action, provides industry with yet another reason to study ways to mimic this mechanism. Much experimental [11][12][13][14][15] as well as computational work [16][17][18] has been done simulating this behaviour and the results obtained indeed prove the effectiveness of a poro-elastic coating over a surface. For instance, a substantial drop in the mean drag, lift, and drag fluctuations, as well as a noteworthy increase in mean lift, has been observed.…”
Section: Introductionmentioning
confidence: 50%
“…Thus, this feature of automatic activation, as opposed to active control techniques which require an energy input to come into action, provides industry with yet another reason to study ways to mimic this mechanism. Much experimental [11][12][13][14][15] as well as computational work [16][17][18] has been done simulating this behaviour and the results obtained indeed prove the effectiveness of a poro-elastic coating over a surface. For instance, a substantial drop in the mean drag, lift, and drag fluctuations, as well as a noteworthy increase in mean lift, has been observed.…”
Section: Introductionmentioning
confidence: 50%
“…The airfoil chord length is 60 mm. The flap length is 10 mm and is mounted flush with the trailing edge of the airfoil, as Schatz et al [2,3] reported this as the location of the flap in their measurements. With a flow speed of 0:51 m=s, this translates to a Reynolds number of Re 30; 600.…”
Section: A Naca0012 Airfoilmentioning
confidence: 97%
“…Schatz et al [2,3] reported that the use of a passive flap near the trailing edge results in a lift increase at high angles of attack. The use of a passive flap is inspired by the feather structure of a bird on the upper side of the bird's wing [4,5].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Shan et al (2008) numerically showed that the active vortex generators controlled by a duty cycle with an excitation frequency equal to the natural frequency of the separation region are more effective than the passive ones for evading the flow separation. Meyer et al (2007) demonstrated that the self-activated movable pop-up flaps fitted on the airfoil enhance the lift by more than 10%, though this device is driven by flow itself, meaning exactly a passive device with no external energy. Similar passive but movable devices, self-adaptive hairy flaps, were investigated by Brücker and Weidner (2014), and they indicated that the hairy flaps of an appropriate flap length can delay the stall without external energy.…”
Section: Introductionmentioning
confidence: 98%